Peroxiredoxin 6 Modulates Insulin Secretion and Beta Cell Death via a Mitochondrial Dynamic Network - Pacifici, Francesca; Della-Morte, David; Capuani, Barbara; Coppola, Andrea; Scioli, Maria Giovanna; Donadel, Giulia; Andreadi, Aikaterini; Ciccosanti, Fabiola; Fimia, Gian Maria; Bellia, Alfonso; Orlandi, Augusto; Lauro, Davide (Frontiers in Endocrinology, 2022)
Glucose stimulated insulin secretion (GSIS) in pancreatic beta cells is controlled by mitochondrial metabolism through ATP production, redox signaling, and calcium (Ca2+) handling. We previously demonstrated as mice knockout for Peroxiredoxin 6 (Prdx6-/-), an antioxidant enzyme with both peroxidase and phospholipase A2 activity, developed a mild form of Diabetes Mellitus with re-duction either in GSIS than peripheral insulin sensitivity. However, whether defect of GSIS presents in Prdx6-/- mice is directly modulated by Prdx6, is still unknown. Therefore, the main goal of the present study was to evaluate whether depletion of Prdx6 may affect directly GSIS and pancreatic beta β-cells function. To achieve this goal, murine pancreatic β-cell line (βTC6) knockdown for Prdx6 (Prdx6KD) was employed, and insulin secretion, ATP and intracellular Ca2+ content were assessed in response to glucose stimulation. Mitochondrial morphology and function were evaluated through electron microscopy and by testing mitochondrial membrane potential, oxygen consumption and mitochondrial mass. Prdx6KD cells showed a significant reduction in GSIS as confirmed by the decrease in both ATP release and Ca2+ influx. GSIS alteration was also associated with a marked impairment of mitochondrial morphology and function, mainly linked to mitofusins downregulation, which are, in turn, strictly related to mitochondrial homeostasis (by regulating autophagy) and cell fate (by modulating apoptosis). Moreover, following a pro-inflammatory stimulus (typical of diabetic sub-jects), and in agreement with the deregulation of mitofusins steady-state levels, we observed an enhanced apoptotic death in Prdx6KD cells compared to control cells. In particular, we analyzed the molecular mechanisms leading to apoptosis, and we further demonstrated as Prdx6 suppression activates both the intrinsic and the extrinsic apoptotic pathways, ultimately leading to caspase 3 and PARP-1 activation. In conclusion, we demonstrated as in pancreatic β-cells, Prdx6 is the first antioxidant enzyme with a pivotal role in GSIS modulation of by controlling mitochondrial homeostasis.